Agrarökonomische Forschung im Kontext der globalen Nachhaltigkeitsziele; Agricultural Economics Research and the Global Sustainable Development Goals - Matin Qaim (German Journal of Agricultural Economics (GJAE), 2019)
– This paper discusses the relevance of agricultural economics research in the context of the United Nations' Sustainable Development Goals. During the last few decades, agricultural economics has made important contributions to hunger and poverty reduction and rural development. Many of the traditional topics of agricultural economics remain important, but several new topics and research questions have also emerged more recently. New topics involve the manifold interactions between agriculture, nutrition, health, the environment, climate change, and societal attitudes. Analysis of these interactions increasingly requires interdisciplinary and systemic approaches. In principle, the agricultural economics profession is well equipped to address such new interdisciplinary topics, but it could do so more confidently and visibly, in order to remain relevant for the big policy topics also in the future.
Keywords: 330; Fehlernährung/Mangelernährung; Malnutrition